Electromechanical reshaping of ex vivo porcine trachea. (17th February 2015) - Hussain, Syed; Manuel, Cyrus T.; Protsenko, Dmitriy E.; Wong, Brian J. F.
<x xml:space="preserve">Abstract</x> Objectives The trachea is a composite cartilaginous structure particularly prone to various forms of convexities. Electromechanical reshaping (EMR) is an emerging technique used to reshape cartilaginous tissues by applying electric current in tandem with imposed mechanical deformation to achieve shape change. In this study, EMR was used to reshape tracheal cartilage rings to demonstrate the feasibility of this technology as a potentially minimally invasive procedure to alter tracheal structure. Study Design Controlled laboratory study using ex vivo porcine tracheae. Methods The natural concavity of each porcine tracheal ring was reversed around a cork mandrel. Two pairs of electrodes were inserted along the long axis of the tracheal ring and placed 1.5 millimeters from the midline. Current was applied over a range of voltages (3 volts [V], 4V, and 5V) for either 2 or 3 minutes. The degree of EMR‐induced reshaping was quantified from photographs using digital techniques. Confocal imaging with fluorescent live and dead assays was conducted to determine viability of the tissue after EMR. Results Specimens that underwent EMR for 2 or 3 minutes at 4V or 5V were observed to have undergone significant (P < .05) reshaping relative to the control. Viability results demonstrated that EMR reshaping occurs at the expense of tissue injury, although the extent of injury is modest relative to conventional techniques. Conclusion EMR reshapes tracheal cartilage rings as a function of voltage and application time. It has potential as a minimally invasive and cost‐efficient endoscopic technology to treat pathologic tracheal convexities. Given our findings, consideration of EMR for use in larger ex vivo tracheal segments and animal studies is now plausible. Level of Evidence N/A. Laryngoscope, 125:1628–1632, 2015